2018
DOI: 10.1016/j.neuroimage.2018.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Lateral prefrontal cortex lesion impairs regulation of internally and externally directed attention

Abstract: Our capacity to flexibly shift between internally and externally directed attention is crucial for successful performance of activities in our daily lives. Neuroimaging studies have implicated the lateral prefrontal cortex (LPFC) in both internally directed processes, including autobiographical memory retrieval and future planning, and externally directed processes, including cognitive control and selective attention. However, the causal involvement of the LPFC in regulating internally directed attention state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…Our neural evidence suggests that these are complementary 41 , rather than contradictory accounts, since we found that focusing on a task, or imagining different people, times, and places, depends on shared neural processes in left DLPFC. Our individual difference analysis suggests DLPFC helps prioritise off-task thought via reductions in the processing of external task-relevant signals 14 , a position supported by evidence that lesions to this region prevent patients ignoring external sensory input 42 . In mechanistic terms, therefore, our data suggests DLPFC may contribute to the decoupling of attention from external input that is thought to be necessary for efficient processing of self-generated information 21 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our neural evidence suggests that these are complementary 41 , rather than contradictory accounts, since we found that focusing on a task, or imagining different people, times, and places, depends on shared neural processes in left DLPFC. Our individual difference analysis suggests DLPFC helps prioritise off-task thought via reductions in the processing of external task-relevant signals 14 , a position supported by evidence that lesions to this region prevent patients ignoring external sensory input 42 . In mechanistic terms, therefore, our data suggests DLPFC may contribute to the decoupling of attention from external input that is thought to be necessary for efficient processing of self-generated information 21 .…”
Section: Discussionmentioning
confidence: 61%
“…Altogether, this emerging literature provides the basis for a hypothesis of the contribution of the DMN in patterns of ongoing thought that future studies could explore. In particular, it will be helpful to use measures of neural function and experience across a wide range of situations to identify how broadly this relationship holds and identifying the causal role of DMN regions by studying populations with deficits within this system (such as Alzheimer’s Disease) and by creating virtual lesions within this system in normal populations using techniques like transcranial stimulation 42 .…”
Section: Discussionmentioning
confidence: 99%
“…When HIV-1 Tg animals were treated with SE at a more advanced age (i.e., 6 to 8 months), the enhancement in sustained attention occurred in a smaller subset (i.e., 40%) of animals and was localized to misses at the shortest signal duration (i.e., 100 msec; Moran et al 2019). Notably, the assessment of two attentional domains in the present study tapped multiple regions of the prefrontal cortex (PFC), with the medial PFC (mPFC) having a primary role in sustained attention (Kim et al 2016), whereas the lateral PFC plays a more prominent role in selective attention (Kam et al 2018). SE treatment relatively early in the course of viral protein exposure (i.e., 2 to 3 months), therefore, enhances sustained and selective attention in a global manner, targeting both hits and misses across signal durations.…”
Section: Discussionmentioning
confidence: 81%
“…Classical accounts of lateral PFC emphasize its role in high-level regulatory processes, such as executive control and working memory (Barbey et al 2013;Miller & Cohen 2001). Human patients with focal lesions in lateral PFC show marked deficits in these domains (Kam et al 2018). More recent approaches have parcellated lateral PFC into distinct subcomponents which manage hierarchical generation, planning and execution of goals together with other PFC regions (Pezzulo et al 2018).…”
Section: Information Seeking Brain: Evidence From Adultsmentioning
confidence: 99%